Features of morpho functional changes in periodontal structures in rats with the presence of a photo of a polymer or cement seal - Varakuta, О. А.; Kushch, O. G.; Варакута, Ольга Анатоліївна; Кущ, Оксана Георгіївна (My University, 2020)
High prevalence of caries is a great public health burden. To choose the optimal filling material for the restoration of hard tissues of teeth in caries patients is quite relevant. When choosing materials for dental restoration the doctor is guided by aesthetics quality, long-term guarantee of therapy, comfort at work and cost/quality ratio. The objective: under the conditions of an experiment to establish the relationship between the morphorfunctional state of periodontal components in the presence of either photopolymeric or cement filling and compare the data obtained with the results of intact animals. Materials and methods. The jaws of 41 white laboratory rats were used. 3 groups were formed: group 1 - intact; group 2 included animals with a photopolymer filling; group 3 consisted of rats with a cement filling. Histobacteriological, immunohistochemical, histochemical and statistical methods were used. Results: the animals with photopolymer filling material, in contrast to animals of the intact group, and those with cement filling, had a greater number of microbial cells in the biofilm during the whole experiment. The microbial cells exhibited enzymatic activity, against which there was a reduced number of glycosaminoglycans in the intercellular substance of the epidermis. Conclusions: Against the background of microorganisms increase in the biofilm of the epithelium, changes in carbohydrate-containing biopolymers of the biofilm, reducing the total number of glycosaminoglycans in animals with photopolymer filling material, the 301 number of lymphocytes and functional activity of antigen-presenting cells in the lamina propria of the gums took place. This indicates the activation of humoral nonspecific and specific links of immunity.
Keywords: photopolymeric filling; cement filling; carbohydrate-containing biopolymer; morphorfunctional state of periodontium